2009
DOI: 10.1097/01.ncc.0000343368.06247.74
|View full text |Cite
|
Sign up to set email alerts
|

Taste and Smell Changes in Patients Receiving Cancer Chemotherapy

Abstract: Few studies have described how patients receiving chemotherapy experience taste/smell changes (TSCs). Food and meal situations have important meaning beyond nutrition, so these common symptoms may affect daily lives. This study aims to investigate distress and impact on daily life from TSCs in patients receiving cancer chemotherapy, analyze reported levels of distress and impact on daily life from TSCs with regard to sociodemographic and clinical factors, and explore patients' reports of self-care strategies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 92 publications
3
12
0
2
Order By: Relevance
“…Moreover, asthma was a predictor of poor olfactory function in patients with chronic rhinosinusitis 37. Some clinical studies have also demonstrated that smell function is significantly decreased in patients receiving cancer chemotherapy,38 39 and at least one study suggest that the prevalence of self-reported taste and smell alterations could reach as high as 86% 40. Of note, smoking was not associated with the prevalence of smell impairment in our cross-sectional analysis.…”
Section: Discussionmentioning
confidence: 43%
“…Moreover, asthma was a predictor of poor olfactory function in patients with chronic rhinosinusitis 37. Some clinical studies have also demonstrated that smell function is significantly decreased in patients receiving cancer chemotherapy,38 39 and at least one study suggest that the prevalence of self-reported taste and smell alterations could reach as high as 86% 40. Of note, smoking was not associated with the prevalence of smell impairment in our cross-sectional analysis.…”
Section: Discussionmentioning
confidence: 43%
“…The change in taste and smell sensitivity among patients receiving chemotherapy is a well-known effect (Bernhardson, Tishelman, & Rutqvist, 2009; Duffy, Fast, Lucchina, & Bartoshuk, 2002), and these have an impact on the patient's day-to-day life (Bernhardson et al, 2009). This knowledge, together with the description from this study of the importance of fresh air and being able to inhale good, outdoor smells, demonstrates the importance of an environment that offers the chance to open a window.…”
Section: Discussionmentioning
confidence: 99%
“…Although alteration of taste (dysgeusia) is a nonlethal condition that is often ignored, taste is critical to the pleasure of eating, which is a major part of QOL [1,2]. Dysgeusia is frequent in patients with cancer [3,4].…”
Section: Introductionmentioning
confidence: 99%